2005
DOI: 10.1542/peds.2004-2001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Impaired Fasting Glucose and Its Relationship With Cardiovascular Disease Risk Factors in US Adolescents, 1999–2000

Abstract: These data, representing 27 million US adolescents, reveal a very high prevalence of IFG (1 in 10 boys and 1 in 25 girls) among adolescents; the condition affects 1 in every 6 overweight adolescents. Adolescents with IFG have features of insulin resistance and worsened CVD risk factors. Evidence for prevention is still forthcoming in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
119
10
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 27 publications
14
119
10
5
Order By: Relevance
“…Even though the prevalence of DM2 in people under 20 years of age has been reported as 0.22% in other countries 35 , we did not find any cases in our sample, probably due to limited power. We did find, however; a surprisingly high prevalence of IFG in adult participants (13.6%), actually higher than that reported for North Americans under age 20 (7.0%) 36 , but unlike the North American report, we found no significant difference between genders.…”
Section: Discussioncontrasting
confidence: 99%
“…Even though the prevalence of DM2 in people under 20 years of age has been reported as 0.22% in other countries 35 , we did not find any cases in our sample, probably due to limited power. We did find, however; a surprisingly high prevalence of IFG in adult participants (13.6%), actually higher than that reported for North Americans under age 20 (7.0%) 36 , but unlike the North American report, we found no significant difference between genders.…”
Section: Discussioncontrasting
confidence: 99%
“…8 Several studies suggest that the long-term damage of end-organs associated with diabetes may start in prediabetes. [9][10][11] In 2012, United Healthcare reported in Health Affairs that adults with diabetes have an average annual health care expenditure of $11,700 per person, whereas adults without diabetes have an average annual expenditure per person of $4400. 12 …”
Section: Introductionmentioning
confidence: 99%
“…The latter has been ascribed to different factors such as insulin resistance, activation of the sympathetic nervous system and an abnormal production of substances by adipose tissue. 6 Several papers have reported that office BP levels correlate with metabolic and inflammatory markers in children as well as in adults; [7][8][9][10][11] however, the precise mechanisms involved in starting and maintaining childhood obesity-related hypertension in the office environment, and even more so in ambulatory conditions, are still unknown. Further insight into the pathophysiology of hypertension affecting young obese people can be obtained by exploring the relation between BP levels measured with ambulatory BP monitoring (ABPM) and a number of factors that might be involved in their elevation.…”
Section: Introductionmentioning
confidence: 99%